2015
DOI: 10.1016/s2214-109x(15)00100-x
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF versus sputum microscopy as the initial diagnostic test for tuberculosis: a cluster-randomised trial embedded in South African roll-out of Xpert MTB/RIF

Abstract: Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
223
2
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 197 publications
(232 citation statements)
references
References 9 publications
5
223
2
2
Order By: Relevance
“…The XTEND study found no evidence of a difference in mortality risk (91 [4%] of 2324 vs 116 [5%] of 2332; adjusted risk ratio 1·10, 95% CI 0·75-1·62). 11 We estimated the years lived with disability of its participants using the number of days with tuberculosis symptoms, assuming symptoms either stopped 2 weeks into treatment, continued to death, or stopped within 2 weeks of not returning to care. We applied disability weights used in the Global Burden of Disease 2010.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The XTEND study found no evidence of a difference in mortality risk (91 [4%] of 2324 vs 116 [5%] of 2332; adjusted risk ratio 1·10, 95% CI 0·75-1·62). 11 We estimated the years lived with disability of its participants using the number of days with tuberculosis symptoms, assuming symptoms either stopped 2 weeks into treatment, continued to death, or stopped within 2 weeks of not returning to care. We applied disability weights used in the Global Burden of Disease 2010.…”
Section: Discussionmentioning
confidence: 99%
“…First, by reducing time with tuberculosis, Xpert might reduce the transmission of tuberculosis. However, the XTEND study 11 found no evidence for differences in time to treatment, the factor most likely to affect transmission. Second, increased diagnosis and survival from tuberculosis might increase antiretroviral therapy costs.…”
Section: Study Design and Participantsmentioning
confidence: 93%
See 2 more Smart Citations
“…), and lack of impact assessment have also hampered its rollout. Insufficient focus has been afforded to effective linkage to care of diagnosed patients, and clinical impact has been blunted by weak health-care delivery systems, as shown by pragmatic trials in high burden settings [6,7]. In many countries, the private sector plays a major role in TB care, yet this sector has limited access to subsidized pricing [8].…”
Section: Who-endorsed Molecular Tb Testsmentioning
confidence: 99%